A luta pela terra: o caso do pré-assentamento irmã Dorothy em Barbosa Ferraz – PR - Jorge, Aline Albuquerque (2019)
The struggle for the land, in the broadest sense, for the agrarian reform, is the chosen path by many peasants, which in the course of territory transformation, were expelled and expropriated from the countryside. To shape this struggle, occupation and the formation of campsites are trumps used by workers, in the sense of pressuring the public power with regard to expropriation and to the creation of settlement projects, set as territory fractions destined to agrarian reform, and consequently, the peasant reterritorialization. To understand the struggle's process for the land, as well as the difficulties and the challenges experienced by peasants, this paper focuses on Irmã Dorothy pre-settlement, located in the municipality of Barbosa Ferraz, in the microregion of Campo Mourão. The history of this pre-settlement started in November 2005, when a group of families bounded to the Landless Workers' Movement (MST) occupied the area of 573,20 hectares, corresponding the Fazenda São Paulo and the Sítio São Vicente. Understanding the questions related to this conflict is important since it means to understand a context that is not exclusive to a singular group, and also that represents the reality of the peasant's struggle in the entire State